FOSTERING STUDENTS’ CRITICAL THINKING SKILLS THROUGH HIGH-LEVEL QUESTIONING IN ANALYTICAL EXPOSITION TEXT - Muhammad Handi Gunawan; Erma Rahmawati; Didi Suherdi; Anni Kristanti Yunandami (University of Kuningan, 2022)
This study employed classroom action research and was conducted in two cycles. The main data were students’ written texts taken from the first cycle and the second cycle, and the teacher’s field notes. The texts were analyzed by examining the schematic structure and the linguistic features of an analytical exposition text. To measure students’ critical thinking, the texts were examined using the Critical Thinking Value Rubric developed by the Association of American Colleges and Universities (AACU). The findings showed that there are positive implications for the application of high-level questioning in students’ critical thinking skills. Furthermore, in comparison between the data gained in the first cycle and the second cycle, it shows that after the implementation of high-level questioning there are some improvements in all aspects of the critical thinking criteria such as issue, evidence, the influence of context, and conclusion based on the value rubric. Although there are some improvements, in terms of delivering the issue, and showing evidence, the students still have difficulties in explaining and elaborating their ideas clearly.Keywords: analytical exposition text; critical thinking; high-level questioning.